The Age Pay Gap between Young and Older Employees in Italy: Perceived or Real Discrimination against the Young? - Castagnetti, Carolina; Rosti, Luisa; Töpfer, Marina (Research in Labor Economics, 2020)
This paper analyzes the age pay gap in Italy (22%), particularly as it is of interest in an aging society and as it may affect social cohesion. Instead of the traditional approach for model selection, we use a machine-learning approach (post double robust Least Absolute Shrinkage Operator [LASSO]). This approach allows us to reduce Omitted Variable Bias (OVB), given data restrictions, and to obtain a robust estimate of the conditional age pay gap. We then decompose the conditional gap and analyze the impact of four further potential sources of heterogeneity (workers', sectors', and occupations' permanent heterogeneity as well as sample selection bias). The results suggest that age discrimination in pay is only perceived but not real in Italy for both men and wome
Keywords: Age pay gap; Perceived discrimination; Machine learning; Italian labour market; Omitted variable bias; Oaxaca-Blinder decomposition